Motivasi Mahasiswa dalam Memilih Bekerja Paruh Waktu: Studi Kasus pada Mahasiswa Prodi Sosiologi Universitas Muhammadiyah Malang - Humayra, Siti; Kumalasari, Luluk Dwi (Jayapangus Press, 2025)
Motivation is an internal drive that directs individuals to act in order to achieve specific goals. In the context of university students, motivation plays a crucial role in decision-making, especially when choosing to engage in part-time work. These decisions may stem from financial needs, a desire to gain experience, or aspirations for financial independence. This study aims to explore the motivations of Sociology students at Universitas Muhammadiyah Malang in choosing part-time employment. The research employs a qualitative approach using a case study method involving five students who are currently working part-time in the Malang area. Data were collected through structured in-depth interviews and participatory observation. The analysis is framed using Max Weber’s theory of social action, particularly focusing on goal-oriented and instrumental rational actions. The findings indicate that students’ motivations for working part-time include using their free time productively, gaining experiences beyond academic settings, easing their parents' financial burdens, and fulfilling lifestyle needs. These students also demonstrate the ability to manage their time effectively by choosing flexible jobs and utilizing work hours to complete academic tasks. Theoretically, this study contributes to strengthening the application of Weber’s social action theory in understanding individual behavior in contemporary student life. Practically, the results provide valuable insights for educational institutions to develop supportive policies for working students, such as flexible class schedules, academic counseling services, and access to part-time job opportunities relevant to their field of study.